al-Lugah as-Sāmiyah - Mandrasi Amirah (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2017)
Abstract            The so-called “As-Sāmiyyūn” (Semitic) are in fact Arab tribes migrated by natural factors from the Arabian Peninsula in search of water and grassland, and the people that established in this part of Western Asia civilizations are linked linguistically and historically as well as in terms of genealogy. Semitic language means a dialect of language of the inhabitants of the southern part from Western Asia bordered by Jordan in the North and the Arabian Sea in the South, the Gulf of ‘Ajam in the East and the Red Sea in the West. The Semitic language has been known universally for the language of those inhabitants and was used for the first time in the 18th century A.D, while the westerners divided the languages of the world by similarities between those languages to the Arabic, Hebrew, Habashiya, Syriac, Assyrian, Aramaic and other languages. This article aims to learn the Semitic language through division in different ages included the general observation on its history, its characteristics and its division.Keywords: the Semitic language, the history of Semitic language, the characteristic of Semitic language, the division of Semitic language.       اللغة الساميةبقلم: مندراسي عميرة سعيدةجامعة دار السلام كونتور ملخصإن الشعوب التي أطلق عليها خطأ اسم "الساميون" هي في حقيقة الأمر قبائل عربية هاجرت بفعل العوامل الطبيعية من جزيرة العرب بحثاً عن الماء والكلأ، و الشعوب التي أنشأت في هذا الجزء من غرب آسيا حضارات ترتبط لغوياً وتاريخياً، كما ترتبط من حيث الأنساب،  وأما المراد باللغة السامية من اللهجات سكان القسم الجنوبي من غرب آسيا من حدود الأردن شمالا إلى البحر العربي جنوبا، ومن خليج العجم شرقا إلى البحر الاحمر غربا.وقد اختار العالمي اصطلاح اللغات السامية لإطلاق على هذه اللغات، ويعد أول من استخدام هذا الوصف، وذلك في القرن الثامن عشر الميلادي. والغربيون يقسمون لغات العالم أوجه شبه بين مجموعة اللغات العربية والعبرية والحبشية والسريانية والآشورية والآرامية وغيرها من اللغات. تهدف هذه المقالة إلى معرفة اللغة السامية عبر القسمة في العصور المختلفة. وهي تشمل المباحث العامة عن تاريخه خصائصه، وقسمته.الكلمات الرئيسية: اللغة السامية، تاريخ اللغة السامية، خصائص اللغة السامية، قسمة اللغة السانية.